The Involvement of miR-23a/APAF1 Regulation Axis in Colorectal Cancer - Fung Lin Yong (International Journal of Molecular Sciences, 2014)
Recent advances in microRNAome have made microRNAs (miRNAs) a compelling novel class of biomarker in cancer biology. In the present study, the role of miR-23a in the carcinogenesis of colorectal cancer (CRC) was investigated. Cell viability, apoptosis, and caspase 3/7 activation analyses were conducted to determine the potentiality of apoptosis resistance function of miR-23a in CRC. Luciferase assay was performed to verify a putative target site of miR-23a in the 3'-UTR of apoptosis protease activating factor 1 (APAF1) mRNA. The expression levels of miR-23a and APAF1 in CRC cell lines (SW480 and SW620) and clinical samples were assessed using reverse transcription-quantitative real-time PCR (RT-qPCR) and Western blot. We found that the inhibition of miR-23a in SW480 and SW620 cell lines resulted in significant reduction of cell viability and promotion of cell apoptosis. Moreover, miR-23a up-regulation was coupled with APAF1 down-regulation in CRC tissue samples. Taken together, miR-23a was identified to regulate apoptosis in CRC. Our study highlights the potential application of miR-23a/APAF1 regulation axis in miRNA-based therapy and prognostication.